An Analysis of Implications of Remittances on The Economic Growth of Nepal - Adhikari, Sabitri Devi Acharya (Economic Journal of Development Issues, 2022)
Migration and remittances are two themes that have received much attention among the policymakers in recent years in Nepal. The pressing need to understand the implication of this inflow of remittances on economic growth has become critical. Yet the existing literature produces inconclusive results. While some research reveals a favorable benefit, others show a negative implication on economic growth, creating the situation of policy uncertainty. This paper seeks to address this ambiguity by providing the fresh result into the implication of remittance from international migration on economic growth of Nepal. To examine this relationship, an ARDL model is employed for the yearly time series data of Nepal for the last 43 years. The analysis reveals co integration among remittances, GDP, total consumption, and capital formation of private sector. The findings reveal a positive impact of remittances on the short-run economy, indicating an immediate boost to economic growth. However, in the long run, as the influence of remittances exhibits a negative trend. It could lead to an 11% decrease in real GDP of Nepal in the long run if there is an increase in remittances by 10 percent. This study contributes to the existing body of knowledge by offering updated empirical evidence on the relationship between remittances and economic growth in Nepal.